Effects of Environmental Enrichment on Doublecortin and BDNF Expression along the Dorso-Ventral Axis of the Dentate Gyrus - Gualtieri, Fabio; Brégère, Catherine; Laws, Grace C.; Armstrong, Elena A.; Wylie, Nicholas J.; Moxham, Theo T.; Guzman, Raphael; Boswell, Timothy; Smulders, Tom V. (Frontiers in Neuroscience, 2017)
Adult hippocampal neurogenesis (AHN) in the dentate gyrus is known to respond to environmental enrichment, chronic stress, and many other factors. The function of AHN may vary across the septo-temporal axis of the hippocampus, as different subdivisions are responsible for different functions. The dorsal pole regulates cognitive-related behaviors, while the ventral pole mediates mood-related responses through the hypothalamic–pituitary–adrenal (HPA) axis. In this study, we investigate different methods of quantifying the effect of environmental enrichment on adult hippocampal neurogenesis in the dorsal and ventral parts of the dentate gyrus (dDG and vDG). To this purpose, 11-week-old female CD-1 mice were assigned for 8 days to one of two conditions: the environmental Enrichment (E) group received i) running wheels, ii) larger cages, iii) plastic tunnels, and iv) bedding with male urine, while the Control (C) group received standard housing. Dorsal CA (Cornu Ammonis) and DG regions were larger in the E than the C animals. Distance run linearly predicted the volume of the dorsal hippocampus, as well as of the intermediate and ventral CA regions. In the dDG, the amount of Doublecortin (DCX) immunoreactivity was significantly higher in E than in C mice. Surprisingly, this pattern was the opposite in the vDG (C > E). Real-time PCR measurement of Dcx mRNA and DCX protein analysis using ELISA showed the same pattern. Brain derived neurotrophic factor (BDNF) immunoreactivity and mRNA displayed no difference between E and C, suggesting that upregulation of DCX was not caused by changes in BDNF levels. BDNF levels were higher in vDG than in dDG, as measured by both methods. Bdnf expression in vDG correlated positively with the distance run by individual E mice. The similarity in the patterns of immunoreactivity, mRNA and protein for differential DCX expression and for BDNF distribution suggests that the latter two methods might be effective tools for more rapid quantification of adult hippocampal neurogenesis.